2016
DOI: 10.1136/bmjqs-2015-004795
|View full text |Cite
|
Sign up to set email alerts
|

How does audit and feedback influence intentions of health professionals to improve practice? A laboratory experiment and field study in cardiac rehabilitation

Abstract: NTR3251, pre-results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 33 publications
4
49
0
Order By: Relevance
“…This chain is only as strong as its weakest link. Feedback effects can be weakened by information-intention gaps (feedback fails to convince recipients that change is necessary), intention-behaviour gaps (intentions are not translated into action), or behaviour-impact gaps (actions do not yield the desired effect on patient care) 9. The success of national audit programmes depends on local arrangements that promote action as well as measurement 10…”
Section: Pay Attention To the Whole Cyclementioning
confidence: 99%
“…This chain is only as strong as its weakest link. Feedback effects can be weakened by information-intention gaps (feedback fails to convince recipients that change is necessary), intention-behaviour gaps (intentions are not translated into action), or behaviour-impact gaps (actions do not yield the desired effect on patient care) 9. The success of national audit programmes depends on local arrangements that promote action as well as measurement 10…”
Section: Pay Attention To the Whole Cyclementioning
confidence: 99%
“…Therefore, those informed by A&F may be better able to focus their time and resources available for quality improvement more efficiently on those care aspects that need it most. However, previous studies have shown that feedback messages are rejected when recipients do not trust the data, disagree with benchmarks, consider improvement unfeasible, or do not consider the clinical topic an important aspect of care quality [ 6 9 ]. An empirical study showed that health professionals ignored between a third and half of the improvement recommendations when confronted with feedback on multiple quality indicators [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…We believe that the high compliance and the key factors of the persistence of multimodal intervention to control MDROs in LMICs were associated closely to the following issues: (1) practicable A&F interventions on improving quality needs an organizational structure and strong leadership in the institute [19,22]; (2) it is more practicable to transform main components into standardized implementation indicators that can be observed objectively in auditing 35 ; (3) quantitative analysis can help to count or measure what is happening now and guide clinical practices [26]; (4) specifying the working scope of doctors and nurses to construct separate implementation indicators, feedback and education can greatly enhance the intervention implementation; (5) benchmark comparison clearly from feedback report could inspire clinical staff to improve the implementation on those indicators below benchmark e ciently according to the control theory [22,24].…”
Section: Discussionmentioning
confidence: 99%
“…In the monthly feedback group, monthly written feedbacks were delivered to clinical staff and the IPC committees of departments. The written feedback included the mean level of a hospital as the benchmark and department individual level of 40 A&F implementation indicators [24]. In quarterly feedback group, written feedbacks were delivered quarterly, with the other measures the same as the monthly feedback group.…”
Section: Study Settingmentioning
confidence: 99%